Characteristics of a Capable Teacher from the Viewpoints of Students at Shiraz University of Medical Sciences - M Rezaee; M Mirbagheri; F Habibagahi; M.J Rahimi (آموزش پزشکی, 2019)
BACKGROUND AND OBJECTIVE: Today, university professors are one of the most important factors in the education. One of the most routine ways to determine the criteria is opinion polls from students. The aim of this study was to investigate the characteristics of a good capable teacher from the viewpoints of the students of Shiraz University of Medical Sciences. METHODS: In this cross-sectional study during 2017-2018, a descriptive-analytic study was carried out on 371 students of dental, medical and pharmaceutical schools of Shiraz University of Medical Sciences. For data gathering, a questionnaire with twenty four items that consisted of four sections (scholarship, teaching method, personal character and communication skill) was approved. The content validity index for the whole questionnaire was calculated to be 0.78. In order to assess the reliability of the test, one weekly test was performed on a pilot group of 30 participants and the reliability of the questionnaire was determined. Intra-group correlation coefficient was 0.857 Internal consistency based on Cronbach's alpha coefficient was 0.81.The questionnaire was in the form of a Likert questionnaire. Statistical analysis was performed by Chi-Square test, independent t-test and one-way ANOVA by SPPS ver.16. FINDINGS: 348 students were completed and returned the questionnaires. (93.8% participation). The mean and standard deviation of students' age in the study were 21.3 ± 3.42. Based on the viewpoint of the male students "mastery of the teaching lesson" and "teaching method" with 96.24% and 92.48%, respectively were important criteria. The important criteria for a good teacher due to female students viewpoint were "mastery of the teacher was taught" and “eloquence” respectively 96.96% and 88.94%. Significant difference between male and female students’ point of view about "personal character" and "communication ability" observed. (P value was 0.023 and 0.041, respectively) But there was no significant difference in "teaching method" and "scholarship" (P value <0.05). CONCLUSION: The mean of total score of female students’ questionnaire was significantly higher than that of male students. Despite the alignment in the results of some cases in both sexes, however, desirable features of university teachers can be analyzed from a variety of dimensions. It should be noted that the characteristics of a capable teacher are not necessarily the same for different levels of education and gender. Therefore, it is suggested that this topic to be considered in the educational planning of the faculties.